Impact Policies of Higher Education in Colombia (2014)
The trial aims to show the evolution of education policy, from conception as a right, service and public good, and analyzed whether the State is fulfilling its function holistically. It starts from the perspective proposed by Amartya Sen, on education as a differentiator for social and economic development of an individual element, and education as a right and as the State has left to others the educational offer. A description of the strategies that are being promoted in recent years in higher education, and achievements for 2013 is also performed. Finally a reflection on the impact of policies is done whether they are achieving their purpose, and some recommendations on how to address some of problems that still exist in the field of inequality, and achieving effectiveness, sense of purpose and policies of higher education.